Taṭwīr Buku Siswa Bahasa Arab Li al-Kitāb al-Maṣāhib al-Muṣawwar `Alā Mahārah al-Qirā’ah (al-Baḥṡ wa at-Taṭwīr Bi al-Madrasah aṡ-Ṡānawiyyah al-Islāmiyyah al-Ḥukūmiyyah 4 Banda Aceh Li as-Sanah aṡ-Ṡāniyah) - Intan Wahyuni; Buhori Muslim; Nur Chalis (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2022)
Based on the observation at MTsN 4 Banda Aceh, the researcher found a problem that students were unable to find important points in the qiraah text, so it was difficult to understand the text regularly according to the storyline in the text. This is due to the denseness of the text presented in the book and also the writing that is less interesting to read, so that it makes students bored to study the contents of the text. Therefore, the researcher wants to develop this book with an illustrated companion book to help students learn Arabic with an attractive appearance. The purpose of this study was to find out the level of validation and effectiveness of the use of the Illustrated Companion Book that had been developed. This study used the R&D (Research and Development) method, and the research instruments used were direct observation, questionnaire and test. The researcher took 31 students from class VII 1 as a sample. As for the data analysis technique, the researcher used the T-Test formula from the SPSS application. The result obtained from this research is the arabic textbook development process consists of ten steps: “research and information, collecting, planning, develop preliminary form of Illustrated Companion Book, preliminary field testing, main Illustrated Companion Book revision, main field testing, operational Illustrated Companion Book revision, operational field testing, final Illustrated Companion Book revision and dissemination and implementation. And the development of an Illustrated Companion Book based on expert judgment, which is valid with a value of 93.5%. The test result showed that the use of an illustrated companion book is effective in improving students' ability to translate and understand the contents of the text on a regular basis. In a way that is based on the results of the value of Sig. 0.000 < 0.05 which indicates that (Ha) was accepted.